Eficiência global dos equipamentos como instrumento de apoio à redução de custo de manutenção: uma survey na indústria de manufatura - Silva, Glauco Roberto Pereira (2016)
The Brazilian manufacturing industries have faced stiff global competition from factories in Europe, USA and Asia, requiring the same monitoring crucial factors to remain competitive. In general, these companies have performance indicators considered key in comparison units. However, the academic literature in the context of maintenance costs, little has addressed specifically on the impact of the use of OEE - Overall Equipment Effectiveness, indicator used to measure the overall effectiveness of equipment and production systems - in reducing maintenance costs. This work questions the extent to which manufacturing companies in Brazil know the impact on the results of production systems, and more particularly about the cost of maintenance. It also presents the objective of understanding the understanding of business impacts on the TPM and OEE bring about the management of maintenance and the costs of this activity. To achieve this goal, we used an exploratory survey as a practical exemplification, illustrating the results of applying the proposed concepts in industrial maintenance activities in manufacturing companies. The aforementioned results demonstrated that both the TPM and the OEE bring effective contributions to increase productivity, quality and competitiveness, and reduce maintenance costs, and that most of the companies studied have clarity that.